A fair and time‐consistent sharing of the joint exploitation payoff of a fishery. (8th April 2019) - Dahmouni, Ilyass; Vardar, Baris; Zaccour, Georges
Abstract: We consider the problem of efficiently managing a fishery where pollution externalities are present. The open‐access bionomic model is analyzed in an n ‐player differential game framework with two‐state variables, that is, the fish stock and the pollution stock. We characterize the noncooperative feedback‐Nash equilibrium and cooperative solution, and define an egalitarian sharing rule to allocate the joint welfare maximizing payoff over an infinite time horizon, and show that this rule is time consistent. Recommendations for Resource Managers ● Cooperation in management of a fishery where pollution externalities are present yields a higher payoff over time as compared to the noncooperative behavior. ● The dividend of cooperation can be allocated among the fisherpersons according to an egalitarian sharing rule. ● This allocation is time‐consistent, that is, no player will be tempted to deviate from cooperation as time goes by, and the initial agreement is sustainable.